Using the Live Food Enrichment with the Squid Egg Extract on the Quantity and Quality of Rotifer, Brachionus plicatilis O.F. Muller - Suminto Suminto (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2008)
The Objective of the research was to know the effect of live food enrichment of rotifer with squid egg extract on the growth patterns and quality of rotifer, especially the EPA and DHA contents. The experiment method was employed in this research and it carried out in the aquaculture laboratory, Faculty of Fisheries and Marine Sciences, Diponegoro University. The research planning was a completely randomized design with five treatments and three replicates, respectively. The recording data was analyzed to get the variables of rotifer growth patterns and the most of rotifer samples were analyzed EPA and DHA contents in the chemical and biochemical laboratory center, Gajah Mada University. The results showed that the addition of squid egg extract in the culture media of rotifer was highly significant effect (p<0.01) on the specific growth rate, the maximal density, and the final density of rotifer culture. However, there was also highly significsnt effect (p<0.01) on the nutrition quality through EPA and DHA contents. To increase the quantity and quality of rotifer, B. plicatilis O.F. Muller in the culture was addition of squid egg extract of 1,2 g/1 million ind. Rotifers during twelve two hours in the rotifer culture. Key word : Rotifer, Brachionus plicatilis O.F. Muller, enrichment, quantity and quality, EPA dan DHA